F30. QUINTUPLE HYPOTHESES TARGETED IN SCHIZOPHRENIA: FIGHT FIRE WITH FIRE. (9th April 2019) - Koola, Maju; Sklar, Jennifer; Davis, Whitney; Nikiforuk, Agnieszka; Meissen, John; Sawant-Basak, Aarti; Aaronson, Scott; Kozak, Rouba
Abstract: Background: There are no effective treatments available or on the horizon for cognitive impairments associated with schizophrenia (CIAS) and primary negative symptoms. Cholinergic and glutamatergic systems, alpha-7 nicotinic acetylcholine receptor (alpha-7nAChR), and N-methyl-D-aspartate receptor (NMDA-R) have been implicated in the pathophysiology of CIAS and primary negative symptoms. Seven studies in animals showed that the galantamine-memantine combination was effective for cognition—synergistic benefits were also seen. The galantamine-memantine combination was significantly better for cognition than the donepezil-memantine combination in patients with Alzheimer's disease. There is evidence that kynurenine pathway (KP) metabolites are associated with CIAS and deficit syndrome. Kynurenic acid (KYNA) is elevated in schizophrenia and is an antagonist of the alpha-7nAChR and NMDA-R. The aim of this study was to examine whether the galantamine-memantine combination is effective for CIAS. Methods: In this 6-week open-label clinical trial, three participants with schizophrenia were enrolled; two completed the study. Participants received galantamine ER 24 mg and memantine XR 21 mg for four weeks. Plasma was analyzed for KP metabolites. Results: In a 36-year-old man with schizophrenia, scores improved in five of seven MATRICS Consensus Cognitive Battery (MCCB) domains; the exceptions were working memory and verbal learning. Also, the Scale for the Assessment of Negative Symptoms total score decreased from five to zero. This finding is suggestive of primary negative symptoms because the Brief Psychiatric Rating Scale, Simpson Angus Scale, and Calgary Depression Scale for Schizophrenia scores were minimal, and the urinary drug screen was negative at baseline and endpoint. In a 45-year-old man with schizoaffective disorder, there were improvements in speed of processing and working memory. Picolinic acid (PIC) concentration decreased in both participants. KYNA concentration decreased in both participants, and kynurenine concentration decreased in one participant. Discussion: This is the first study that is suggestive of the association of MCCB and KP metabolites in schizophrenia. The decrease in PIC concentration with the treatment is a promising finding because high concentrations of PIC are toxic to the brain. Although this pilot study is not powered, the data are promising. RCTs are warranted to validate the findings. "Repurposing" of approved medications such as galantamine and memantine could lead to rapid clinical implementation if the results of RCTs are positive. This study is the first in which the nicotinic-cholinergic and glutamatergic systems were simultaneously targeted in people with schizophrenia. In addition, the galantamine-memantine combination (unique and novel) has synergistic effects of α7nAChR and NMDA-R. The galantamine-memantine combination targeting both receptors concurrently is a paradigm shift in schizophrenia because until now only one receptor (NMDA or nicotinic with partial treatment response) has been targeted at a time. This combination may broaden the number of cognitive domains that may significantly improve compared to placebo and potentially increase the composite score. The pathophysiological mechanism of mismatch negativity may occur via interactive effects of alpha7nACh and NMDA receptors. This combination targets the quintuple hypotheses (dopamine, nicotinic-cholinergic, glutamatergic/NMDA, GABA, and KYNA) concurrently and has the potential to treat positive, cognitive, and primary negative symptoms. The galantamine-memantine combination has the potential to become the first anti-schizophrenia treatment.